2022
DOI: 10.3390/sym14122603
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Symmetrical Peak Fitting Method Based on Improved WOA Algorithm for the Analysis of Microchip Electrophoresis Signals

Abstract: The problem of overlapping peaks has been a challenge in microchip electrophoresis (ME) signal analysis. However, traditional peak fitting algorithms have difficulty analyzing overlapping peaks due to the high dependence on the starting point. In this study, we propose a symmetrical peak fitting method named the tent-mapped whale optimization algorithm and Levenberg–Marquardt (TWOALM), which combines a whale optimization algorithm (WOA) improved by one of the most commonly used chaotic maps, the tent map and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…To demonstrate the effectiveness of the proposed peak sharpening method, the fitting performance of different algorithms is compared in this section. For the overlapping peak fitting problem, the fitting accuracy of the swarm intelligence algorithms (SLSMA [7], TWOA [8], and PSO [9]), the gradient algorithms (LM [10] and TRR [11]), and the simplex algorithm (NM [12]) are analyzed. Consistent with previous work [7], the population size and maximum number of iterations for the swarm intelligence algorithms in this study are set to 250 and 200, respectively.…”
Section: Results Of Synthetic Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the effectiveness of the proposed peak sharpening method, the fitting performance of different algorithms is compared in this section. For the overlapping peak fitting problem, the fitting accuracy of the swarm intelligence algorithms (SLSMA [7], TWOA [8], and PSO [9]), the gradient algorithms (LM [10] and TRR [11]), and the simplex algorithm (NM [12]) are analyzed. Consistent with previous work [7], the population size and maximum number of iterations for the swarm intelligence algorithms in this study are set to 250 and 200, respectively.…”
Section: Results Of Synthetic Signalsmentioning
confidence: 99%
“…In the last five years, the analysis methods of peak-shaped signals based on optimization algorithms have been proposed. These methods can be classified into three categories, namely, swarm intelligence algorithms [7], [8], [9], gradient algorithms [10], [11], and simplex algorithm [12]. Specifically, the SLSMA [7] and the TWOA [8] were used for the fitting analysis of overlapping ME peaks by exploiting the global optimization capability of the swarm intelligence algorithm.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…To separate the unresolved peaks of magnetic eddy current signal, Xiong et al [17] proposed an unresolved peaks separation algorithm based on the genetic algorithm (GA). Recently, an improved whale optimization algorithm [18] has been applied to the analysis of ME signals. These studies show that the advantages of swarm intelligence algorithms in nonlinear optimization contribute to the analysis of unresolved peaks.…”
mentioning
confidence: 99%
“…However, the SMA algorithm may also suffer from slow convergence when dealing with complex problems [20]. Although it has been shown that the problem of unresolved peaks analysis is a separable nonlinear least squares problem [18], [21], when there are more complex unresolved peaks, the larger number of nonlinear parameters to be optimized is a great challenge for the swarm intelligence algorithm. In addition, to our knowledge, no relevant studies are using the SMA algorithm to analyze unresolved peaks.…”
mentioning
confidence: 99%